The role of employee engagement in the influence of compensation and leadership style on turnover intention in automotive companies - Intan Bayduri; Setyawan, Agustinus (Universitas Muhammadiyah Pontianak, 2026)
Employee turnover remains a critical challenge in the automotive industry. This study examines the effects of compensation and leadership style on turnover intention, with employee engagement as a mediating variable. Data were collected from 281 employees of automotive companies in Jakarta and analyzed using PLS-SEM. The results indicate that compensation and leadership style significantly enhance employee engagement, while employee engagement significantly reduces turnover intention. However, compensation and leadership style do not directly affect turnover intention. Employee engagement fully mediates both relationships. These findings highlight the importance of fostering employee engagement to strengthen retention and reduce turnover intention. Keywords: Compensation; Leadership Style; Employee Engagement; Turnover Intention; Automotive Industry; PLS-SEM